DETERMINANTS OF SHARIA INSURANCE COMPANY PROFITABILITY - Maman Suherman; Irman Firmansyah; Medina Almunawwaroh (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
The growth of sharia insurance in Indonesia continues to occur. This is a sign that the people in Indonesia have good risk management because the company's growth is supported by the increase in customers in sharia insurance companies. This condition must be supported again by the conditions in which the company has a good performance, so the company must find a way to continue to improve its performance. This study is aimed to determine the effect of leverage, firm size, and company age on the financial performance of sharia companies. The method used is through quantitative research using multiple regression. The method of data collection uses a purposive sampling technique carried out to all populations, namely all Islamic insurance companies in Indonesia from 2012 to 2018. The results of the study show that leverage and age of the company do not succeed in influencing financial performance, while firm size has a positive effect on financial performance. Therefore it is important for companies to continue to increase their assets, especially in collecting funds from the public as the company's ingredients in managing their finances to improve their financial performance.Keywords: Age, Financial Performance, Leverage, Size